First record of the subfamily Tersilochinae (Hymenoptera: Ichneumonidae) from New Caledonia - Khalaim, Andrey I. (Zootaxa, 2025)
The subfamily Tersilochinae (Ichneumonidae) is recorded for the first time from New Caledonia. A new species, Diaparsis (Diaparsis) storozhenkoi sp. nov., is described as new to science. The new species is compared with known Australasian Diaparsis species from Papua New Guinea, Australia and New Zealand. Partial identification key to the Australasian species of Diaparsis is provided.